RECKONING OF SPIDER BIODIVERSITY IN BHENDI [ABELMOSCHUS ESCULENTUS L. (MOENCH)] ECOSYSTEM - ARDHENDU CHAKRABORTY,; K. KUMAR,; RIDIP BHATTACHARJEE, (The Bioscan, 2015)
Field surveys were conducted to explore the diversity and abundance of spider fauna in bhendi ecosystem. A total of 24 spider species under 16 genera and 7 families were observed in the bhendi ecosystem. Amongst the spider families, the family araneidae was more diversed consists of maximum 6 species followed by oxyopidae (5 species), salticidae (5 species), tetragnathidae (3 species), lycosidae (2 species), thomisidae (2 species) and clubionidae (1 species). Amongst the different families, salticidae was relatively abundant (36.40 and 28.71% in kharif and rabi respectively) than other families. The species richness (R) of spiders during kharif (2.92) was more than rabi (2.60) seasons. The species evenness (J), Shannon and Wiener diversity index (H’) and Simpson index (ë) of spiders were 0.60 and 0.64, 1.71 and 1.74 and 0.21 and 0.19 during kharif and rabi respectively, indicating the more or less similarity in both the seasons. It was concluded that species richness of spider during kharif was found to be abundant compared to the rabi season and species diversity indices and species evenness indices were more or less equal and exhibited a similar diversification in both the seasons.